(untitled) (Conference Zone, 2022)
The article scientifically analyzes the importance of innovative technologies in improving the quality of education. As well as working methods based on the general professional and special knowledge acquired in the theoretical process, general familiarization with the products, specific production issues, the latest models of the latest equipment and modern production technology, advanced working methods and methods of organizing agriculture on a scientific basis Modern information technologies play a great role in the formation of skills and qualifications for training, practical performance of operations.